Interactive Multimedia as Information Media Parasitic Infection with Multimedia Development Life Cycle Method - Aldo, Dasril; Ilmi, Miftahul; Putra, Sapta Eka; Army, Widya Lelisa (JISA(Jurnal Informatika dan Sains), 2023)
This study focused on the problem of lack of interactive multimedia-based educational information media that is interesting as a provider of information about parasitic infections in humans. This parasitic infection is very dangerous, especially for children who still lack knowledge about it. The aim of this research is to provide educational information media to the wider community, especially at the Seberang Padang Health Center, about parasitic infections in a way that is as interesting as possible and easy to use. Interactive multimedia is a solution to this problem. This research uses the Multimedia Development Life Cycle Method as a guide in building interactive multimedia with the stages of Concept, Design, Material Collecting, Assembly, Testing and Distribution. The results of the alpha test showed that all features of this interactive multimedia can function properly. A beta test was conducted on 30 respondents from the public who accompanied patients to the Seberang Padang Health Center. As a result, this interactive multimedia received a rating of 4.54 out of 5. Therefore, this interactive multimedia is very good and suitable for use as an educational medium for information about parasitic infections. With this interactive multimedia-based educational information media, it is hoped that the wider community can better understand and be aware of parasitic infections and preventive measures that can be taken to avoid these infections.